Reinforced high-strength engineered cementitious composite (ECC) columns under eccentric compression: Experiment and theoretical model. (1st November 2019) - Li, Ling-Zhi; Bai, Yang; Yu, Ke-Quan; Yu, Jiang-Tao; Lu, Zhou-Dao
Highlights: Structural behaviors of reinforced high-strength ECC columns under large eccentric compressive loading were investigated. Parameter analysis of the load-bearing capacity of high-strength plain ECC column was conducted. Feasibility of non-steel bar reinforced column was proved. Abstract: Engineered cementitious composites (ECC) with a tensile rupture strain larger than 3%, has won itself wide attention at the material level. To further investigate its performance at the structural component level, a series of reinforced ECC (R/ECC) columns with the cross-section dimensions of 120 mm × 120 mm were tested under large eccentric compressive loading at the eccentricity of 80 mm. One reinforced concrete (RC) column was also fabricated for reference. The compressive strengths of both ECC and concrete were controlled at 60 MPa. The displacement at half height point, the strains of longitudinal bars and the crack patterns of columns were monitored. The experimental results showed that the peak load of the plain ECC column approached 50% of the value of the RC column with a reinforcement ratio of 4.3% (RC-4.3%). The peak load of R/ECC column was found to gain an increase of 35.2% compared to the RC column with the same reinforcement ratio. The multiple-crack patterns were fully developed along the height of the column. An analytical model was proposed for the load-bearing capacity of R/ECC columns under large eccentric compression, and was validated by the experimental results. Finally, parametric analyses showed that the peak load of plain ECC-90 column (i.e., compressive strength = 90 MPa) was similar to the value of RC-4.3%, while the peak load of plain ECC-120 column (i.e., compressive strength = 120 MPa) exceeded that of RC column, implying that high-strength ECC could be applied to completely replace the steel bars in columns.